Analisis Sanksi Pidana terhadap Pelaku Pengoplosan LPG (Liquified Petroleum Gas) (Postulat, 2023)
LPG has long been an alternative to kerosene. One of the objectives of the kerosene to LPG conversion program in 2007 was to supply fuel that is comfortable, clean, and efficient. Despite the government's intention to help the less fortunate with the LPG gas subsidy program, some individuals have used this as an opportunity to abuse it. Not only was the distribution misdirected, but these individuals misused it for personal gain. They deliberately buy as much subsidized LPG gas as possible and then resell it in mixed form by transferring the contents of the 3 kg of subsidized gas into 12 kg of non-subsidized gas cylinders (Irawan, 2020). Based on this description, the author feels the need to conduct an analysis of several articles that discuss criminal sanctions for mixing LPG. The method used in this study is a normative juridical method with a statutory approach that analyzes all articles related to criminal sanctions for mixing LPG (liquefied petroleum gas). Based on the results of the discussion, the act of mixing subsidized LPG gas cylinders into empty cylinders of 12 kg or 50 kg size is very detrimental and can be regarded as a criminal act. So based on Article 62 paragraph 1 of Law Number 8 of 1999 concerning Consumer Protection, which states that traffickers violate the provisions mentioned in Article 8, Article 9, Article 10, Article 13 paragraph (2), Article 15, Article 17 paragraph (1cerning Consumer Protection, which states that traffickers violate the provisions mentioned in Article 8, Article 9, Article 10, Article 13 paragraph (2), Article 15, Article 17 paragraph (1), letter a, letter b, letter c, letter e, paragraph (2), and number 18, the offender can be punished with imprisonment for a maximum of 5 (five) years or a fine of up to Rp. 2,000,000,000.00 (two billion rupiah).